46.8k views
3 votes
How to solve 5-2x=-4x-7

2 Answers

5 votes

Answer:

Pull out like terms: 12 + 2x = 2 • (x + 6)

Solve: x+6 = 0

Then you get; X=-6

I hope this is right and hopefully it helped you

User Lateesha
by
5.9k points
7 votes

Answer:

x=-6

Explanation:

Use Substitution

so 5-2x=-4x-7

I'ma move that -4x to the other side by making it a positive

5+2x=-7

than I'ma move that 5 to the other side by making it a negative

2x=-12

to isolate the x you dived by both sides by the 2

x=-6

I doubled checked and it's -6

User Greg Howell
by
5.9k points